Problems of Training Highly Qualified Teachers on the Basis of Development Strategy - Karimjanova Dilnoza Alijanovna (Zien Journals, 2023)
The article analyzes the issue of training highly qualified pedagogues based on the development strategy of the new Uzbekistan.
Keywords: Development; strategy; competence; pedagogue